Diagnosis of acquired immunodeficiency virus from a Cryptococcus meningoencephalitis. Case Presentation - María Odeymi Urdanivia Cruz; Idalmis D. Reyes Rod´ríguez; Jorge E. Barletta del Castillo (Medisur)
Cryptococcosis, a mycotic infection, had a sporadic presentation worldwide, but in the last two decades there has been an increase in the incidence of AIDS-related opportunistic infection, even considering it as the most frequent fungal meningitis in these patients. It is a deep mycosis, of a sub acute or chronic course, considered as opportunistic. For such reasons a case of a 32 year old, black patient is presented, with antecedents of bronchial asthma, smoker from 21 years before, alcoholic from 17 years and hypertensive ( three years of evolution) without regular treatment. Four days before admission he started with headache, he was unconscious and Sphincter relaxation. He came to the emergency room of the Gustavo Aldereguía Lima Hospital where he was found to have stiff neck and his BP was de 200/120 mm Hg. His BP was lowered and the patient improved his clinical picture. On questioning he was found to have a disordered life style, without stable partner, on physical examination it was observed oral candidiasis and herpes simple in the lower lip. A rapid test for IDS was realized which resulted positive. He was admitted and microbiological studies of cerebrospinal fluid with Chinese ink staining that showed capsulated levaduriform cells, sign of Cryptococcus meningoencephalitis.